Pengaruh Efektivitas Komite Audit Dalam Meningkatkan Profitabilitas Perusahaan : (Studi Pada Perusahaan BUMN Yang Terdaftar Di BEI Periode 2018-2021) - Muhammad Catur Pamungkas; Lego Waspodo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of audit committee effectiveness in increasing company profitability. The sampling technique used in this research was purposive sampling. The type of data used is secondary data. The type of research used is quantitative research with data collection techniques, namely downloading the annual reports of state-owned companies listed on the IDX. The data analysis technique in this research was carried out using the SPSS 26 method. The results of this research show that the independence of the audit committee and the competence of the audit committee have a positive and significant effect on profitability. Meanwhile, the number of audit committees and the frequency of audit committee meetings have no effect on profitability.